Identifikasi Zona Prospek Panas Bumi Berdasarkan Analisis HVSR di Sekitar Nagari Malampah (Lembaga Pengembangan Kinerja Dosen, 2026)
Nagari Malampah, Tigo Nagari District, Pasaman Regency, West Sumatra, is located in a volcanic and tectonic environment that supports the development of a geothermal system. Information regarding the distribution of relatively more prospective areas in the region remains limited. This study aims to estimate the distribution of geothermal prospect zones using the Horizontal-to-Vertical Spectral Ratio (HVSR) method based on microtremor data from 16 measurement points. HVSR analysis provides the dominant frequency (f₀) and amplification factor (A₀) parameters. These parameters were integrated using a scoring system based on their respective classes to determine relatively low, moderate, and high prospect zones. The analysis indicates that the relatively high prospect zones are located at measurement points T5, T6, T8, and T10. These results indicate variations in site response and subsurface impedance contrasts that are relatively more supportive of geothermal prospects at several locations. This interpretation represents an initial indication of geothermal prospectivity and cannot be used to directly confirm the presence of hydrothermal fluids. Further validation is required using geological, geochemical, resistivity, magnetotelluric (MT), or other exploration data.